Quality of Life of Kuzbass Coal Industry Workers - Svetlana N. Raudina; Victor A. Semenikhin; Andrey G. Petrov (Acta Biomedica Scientifica)
The study of the quality of life (QoL) in medicine is recognized worldwide, its scientific study is also recognized as a priority.Aim. To study the quality of life of workers in the Kuzbass coal industry, who are exposed to physical factors, as well as to assess the severity and degree of influence of diseases on QoL.Methods. The method of QoL assessment was based on of individual QoL assessment and the rationing of intensive indicators. For the subjective assessment of the severity of symptoms of the occupational disease (OD) and the effect of these symptoms on QoL, we used the questionnaire method, recommended by Dyakovich M.P. and Kazakova P.V. (2013).Results. The study of individual QoL included 400 miners with OD, caused by exposure to physical factors. We found that among the low indices, reflecting determination of quality of life of workers in the coal industry, satisfaction with the past was the highest. Indices of satisfaction with the future were the lowest. The predominance of subjective positive over negative was possibly related to social satisfaction.The study involved a group of 98 patients, who had symptoms of diseases, caused by exposure to physical factors. Subjective assessment of patients with sensorineural hearing loss (SHL) revealed a significant effect of symptoms of the disease on QoL, especially with regard to symptoms that worsened their psycho-emotional state, which might further lead to impairments and disabilities.Conclusion. Evaluation of individual QoL, as well as the severity of the symptoms and their effect on QoL, helps correctly diagnose the patient’s personal response to the disease, and to evaluate the effectiveness of treatment. In the future, doctors can use the received information when developing rehabilitation measures.